BALANCE BETWEEN THE ECONOMY AND THE ENVIRONMENT - Herlambang, Embang; Syahrul Ansari, Teuku; Budi Santoso, Imam; Yunus, Muhammad (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Economy and environment are variables contained in the principles of sustainable development which underlie legal regulations related to the environment in various countries in the world. Nevertheless, there is still environmental pollution and damage that occurs, such as air pollution caused by industrial activities from fertilizer factories that produce ammonia-based fertilizer which pollutes the air in residential areas around the factory, which shows an imbalance between the economy and the environment. On the one hand, this economic activity is an effort aimed at creating community welfare, but on the other hand, this activity causes disruption to the community in obtaining a good living environment. The results of this research show that ammonia gas is a compound produced from the fertilizer industry process which is toxic and pollutes the environment. Ammonia is a poisonous gas, colorless and has a distinctive odor which can cause problems with human health and even death. However, the ammonia gas that spreads to residential areas around the factory is caused by wind blowing towards the settlement and this is not dangerous, because the wind blows the levels of ammonia gas to decrease. However, the presence of an ammonia-based fertilizer factory does not necessarily mean that society is free from the threat of this gas, because there have been several incidents of ammonia gas leaks in various parts of the world which have caused material losses and claimed many lives.